Crowd Violence Handling: Case Study Of Magelang City District Police - Nugroho Ari Setyawan (Jurnal Litbang Polri, 2022)
Crowd violence endangers human lives and has proximity to crime-related problems. This study discusses the crowd violence handling of the Magelang City district police. Participatory research, action research, and document analysis are applied to unearth the phenomena. Youngsters are seen as the dominant participants of crowds which implicates how the police shall reconsider their policing approach. Cooperation with relevant parties is needed to endeavour more law-abiding adolescents. Moreover, the crowd violence prevention strategies the at district police level shall be established and reviewed periodically to find better and more appropriate methods. Hence, crowd violence may be reduced and prevented for the advantage of broader society.